THE EFFICIENCY OF MANUAL THERAPY WITH COMBINED CRYOULTRASOUND TECHNOLOGY IN THE FUNCTIONAL REHABILITATION OF CHRONIC PLANTAR FASCIITIS - George Sebastian IACOB (Editura Universitatii Transilvania din Brasov, 2020)
Plantar fasciitis (PF) is an inflammatory process of the plantar fascia, commonly encountered among runners. The purpose of this study is to evaluate whether the manual therapy (MT) alternated with the use of cryoultrasound in the treatment of PF is an effective option in reducing the symptomatology. The test was performed on 10 subjects (two groups), having the following rehabilitation protocol: Group A - MT and cryoultrasound; Group B - MT and cryotherapy. Both treatments proved to be effective, the difference in pain intensity on the VAS scale between the two groups measured at E3 being 10.48% in favor of group A.